Effects of Static and Dynamic Exercises on Core Muscle Strength and Endurance - Monika Kibildaitė; Diana Nemčiauskienė; Laura Žlibinaitė (Lithuanian Sports University, 2022)
Background. Rehabilitation research is currently focused on the effects of exercise on patients with acute or chronic low back pain. However, there is a lack of preventive research investigating the effects of dynamic and static exercises on the strength and endurance of the core stability muscle in individuals engaged in leisure-time non-professional sports activities. The aim. To determine the effect of static and dynamic muscle exercises on core stability muscle strength and endurance. Methods. The study involved 12 volunteers (20-30 years old) engaged in leisure-time non-professional sports activities that did not experience back pain. Two groups were formed: the first (n = 7), in which the subjects performed static exercises, and the second (n = 5), in which the subjects performed dynamic exercises. The strength and endurance of the core flexor and extensor muscles were assessed at the beginning and end of the study. The study lasted 5 weeks. Exercise sessions were held 3 times a week for 20-30 minutes. Results. Strength and endurance of the core flexor and extensor muscles significantly increased in both groups. Comparing the effects of static and dynamic exercises on core flexor and extensor muscle strength and endurance, a statistically significant difference was observed in the change in core extensor muscle strength. Conclusions. The strength and endurance of the core flexor and extensor muscles increased both after dynamic exercise and static exercise interventions. Core muscle strength increased more after the dynamic exercise intervention. Keywords: core stability, isometric strength, physical therapy, exercise, young individuals.